2021
DOI: 10.1007/s11013-020-09705-2
|View full text |Cite
|
Sign up to set email alerts
|

“A Free People, Controlled Only by God”: Circulating and Converting Criticism of Vaccination in Jerusalem

Abstract: This paper explores how criticism surrounding the ethics and safety of biomedical technologies circulates and ‘converts’ through global–local religious encounters, producing new claims of moral opposition and rights to religious freedom. The paper is concerned with the question of what rhetorical devices make vaccine safety doubt relevant to religiously Orthodox settings and what implications arise? Based on an ethnographic study of vaccine decision-making and non-vaccination advocacy in Jerusalem, the paper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The rhetorical link between perceived deception surrounding COVID-19 vaccines and the Nazi genocide is striking, and it underscores the place of the Shoah as the central reference point in Haredi Judaism (Caplan 2002). It is an example of the circulation and conversion of criticism of vaccination; while vaccines are a globalized technology, safety concerns arise at local levels and transform into historically, politically, religiously, and socially situated metaphors (Kasstan 2021b). The pashkevil and its content reflect what Ilana Gershon (2010: 290) would term a "media ideology," where persuasiveness of rhetoric and receptiveness is "fundamentally influenced by local concepts of selves, relationships, and communication."…”
Section: Public Warningsmentioning
confidence: 99%
“…The rhetorical link between perceived deception surrounding COVID-19 vaccines and the Nazi genocide is striking, and it underscores the place of the Shoah as the central reference point in Haredi Judaism (Caplan 2002). It is an example of the circulation and conversion of criticism of vaccination; while vaccines are a globalized technology, safety concerns arise at local levels and transform into historically, politically, religiously, and socially situated metaphors (Kasstan 2021b). The pashkevil and its content reflect what Ilana Gershon (2010: 290) would term a "media ideology," where persuasiveness of rhetoric and receptiveness is "fundamentally influenced by local concepts of selves, relationships, and communication."…”
Section: Public Warningsmentioning
confidence: 99%
“…21,22 Attention to non-vaccination activism has highlighted the strategies that activists use to promote their cause and specifically to target selfprotective religious minorities. 23 Scholars also note that pro-vaccine activism takes on situated (context-specific) forms, and illustrates how examining public support for vaccination is helpful to illustrate the kinds of impact that are sought in relation to local context. 24 Orthodox Jewish minorities in Israel, Europe and North America have experienced recurring measles outbreaks and share a common pattern of sub-optimal vaccination coverage.…”
Section: Background: Religion Vaccination and Influences On Decision-makingmentioning
confidence: 99%
“…27 Barriers to vaccination uptake include inflexible services, 25 particularly because of larger family sizes. Additional influences on uptake include misinformation, 23,28 and, in Israel, a reluctance to engage with public health services. 6 Studies exploring non-vaccination among Orthodox Jewish minorities note that perception of risk and safety are primary influences on vaccine decisions.…”
Section: Background: Religion Vaccination and Influences On Decision-makingmentioning
confidence: 99%
“…For example, Smother's et al found that men were more than twice as likely than women to say that they were continuing to attend worship services in person despite government guidelines (Smothers et al 2020(Smothers et al , p. 1067. However, most of these studies focus on one particular religious group, typically Christian (e.g., Campbell 2020), or draw on large scale quantitative data to examine quantifiable questions such as church attendance, adherence to public health guidelines, vaccine uptake (Kasstan 2020(Kasstan , 2021a(Kasstan , 2021b and death rates in hospitals. Combining our different intellectual backgrounds in anthropology and sociology of religion and theology, our study takes a comparative and diverse approach to explore the challenges COVID-19 presents for religious practices and belief; we ask: what new formations of religious life have emerged amidst COVID-19?…”
Section: Religion Change and Covid-19mentioning
confidence: 99%